2019
DOI: 10.1073/pnas.1900644116
|View full text |Cite
|
Sign up to set email alerts
|

Development and evolution of age-dependent defenses in ant-acacias

Abstract: Age-dependent changes in plant defense against herbivores are widespread, but why these changes exist remains a mystery. We explored this question by examining a suite of traits required for the interaction between swollen thorn acacias (genus Vachellia) and ants of the genus Pseudomyrmex. In this system, plants provide ants with refuge and food in the form of swollen stipular spines, protein-lipid–rich “Beltian” bodies, and sugar-secreting extrafloral nectaries—the “swollen thorn syndrome.” We show that this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 50 publications
0
58
0
Order By: Relevance
“…A number of studies have shown that plants over-expressing miR156 are more or less sensitive to various environmental stresses (Stief et al, 2014;Cui et al, 2014;Arshad et al, 2017;Kang et al, 2020), but there is still little evidence that juvenile and adult phases of wild type plants display these same differences, or how they might contribute to plant fitness. There are relatively few examples of phase-specific vegetative traits that are either known or expected to be selectively advantageous (Williams et al, 1998;Holeski et al, 2009;Leichty & Poethig, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have shown that plants over-expressing miR156 are more or less sensitive to various environmental stresses (Stief et al, 2014;Cui et al, 2014;Arshad et al, 2017;Kang et al, 2020), but there is still little evidence that juvenile and adult phases of wild type plants display these same differences, or how they might contribute to plant fitness. There are relatively few examples of phase-specific vegetative traits that are either known or expected to be selectively advantageous (Williams et al, 1998;Holeski et al, 2009;Leichty & Poethig, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…smRNA levels were measured by RT-qPCR, using primers specific for mature sequences of miR156, miR157 and miR159 in combination with the stem-loop RT 6 primers described in Varkonyi-Gasic et al (2007) (Table S2). miR159 was used as an endogenous control (Leichty & Poethig, 2019) and validated across time points in seed-grown and culture derived plants (Fig. S2).…”
Section: Mrna and Smrna Abundancementioning
confidence: 99%
“…Vegetative phase changes have also been described in other species such as Acacia confusa , Acacia colei , Eucalyptus globulus , Hedera helix , Quercus acutissima , Populus , Oryza sativa , and Nicotiana tabacum [ 6 , 7 , 8 , 9 ]. The juvenile-to-adult phase change, referred to as the vegetative phase change, is unidirectional and associated with certain physiological responses [ 2 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The juvenile-to-adult phase change, referred to as the vegetative phase change, is unidirectional and associated with certain physiological responses [ 2 , 10 , 11 ]. For example, the age-dependent production of swollen thorns by members of the genus Vachellia is correlated with the expression of vegetative phase change markers [ 9 ]. These swollen thorns provide food for ants while the ants protect the plant from pathogens and herbivores.…”
Section: Introductionmentioning
confidence: 99%
“…A temporal decline in miR156/miR157 during shoot development leads to an increase in expression of their target genes— SQUAMOSA PROMOTER BINDING PROTEIN-LIKE ( SPL ) transcription factors—which promote the adult phase (Wu and Poethig, 2006; Wu et al, 2009). This temporal mechanism is widely conserved and regulates shoot identity in diverse plant lineages (Chuck et al, 2007; Leichty and Poethig, 2019; Riese et al, 2008; Wang et al, 2011). SPL genes are known to promote the expression of miR172, which initiates adult development through repression of its targets in the APETALA2-LIKE ( AP2-LIKE ) gene family.…”
Section: Introductionmentioning
confidence: 99%